Місце назофарингіальної протекції та оксигенації в периопераційному управлінні дихальними шляхами пацієнтів з ожирінням - Воротинцев, Сергій Іванович; Воротынцев, С. И.; Vorotyntsev, S. І. (My University, 2017)
В роботі проведене дослідження ефективності використання назофарингіального повітроводу у пацієнтів з ожирінням під час апное перед інтубацією трахеї та в ранньому післяопераційному періоді. Виявлено, що після преоксигенації з використанням тільки лицьової маски, десатурація нижче 95% при послідуючому апное наступає в середньому через 144±25 сек., тоді, як додаткова оксигенація через назофарингіальний повітровід з потоком кисню 5 л/хв. збільшує час безпечного апное до 4 хв. у 85% пацієнтів (p<0,05). Післяопераційна гіповентиляція виникає у 100% пацієнтів з ожирінням, що пов’язано як з депресією дихання, внаслідок використання наркотиків, так і з обструкцією верхніх дихальних шляхів. Останнє може бути попереджено у 100% пацієнтів застосуванням назофарингіального повітроводу. В работе проведено исследование эффективности использования назофарингеального воздуховода у пациентов с ожирением во время апноэ перед интубацией трахеи и в раннем послеоперационном периоде. Выявлено, что после преоксигенации с использованием только лицевой маски, десатурация ниже 95% при последующем апноэ наступает в среднем через 144±25 сек., тогда, как дополнительная оксигенация через назофарингеальный воздуховод с потоком кислорода 5 л/мин. увеличивает время безопасного апноэ до 4 мин. у 85% пациентов (p<0,05). Послеоперационная гиповентиляция возникает у 100% пациентов с ожирением, что связано как с депрессией дыхания, вследствие использования наркотиков, так и с обструкцией верхних дыхательных путей. Последнее может быть предупреждено у 100% пациентов применением назофарингеального воздуховода. Oxygenation support during intubation and after extubation of trachea is extremely important for patients with obesity because they have a high risk of difficult airways and postoperative obstruction. That’s why patients with obesity should be put in head-up position both during the induction of anesthesia and during awakening; they also need the application of continuous positive airway pressure (CPAP), the use of different techniques of oxygenation and protection of upper airways. Among these techniques we purchased nasopharyngeal airway (NPA) application and set out to check its effectiveness for the increase of the time of safe apnea before tracheal intubation and prevention of the obstruction of upper airways during recovery after anesthesia. The research included 40 patients with a body mass index (BMI) over 30 kg/m2 that were planned to be laparoscopically operated under general anesthesia with mechanical ventilation. All the patients had Mallampati score of I and II, thyromental distance more than 6 cm, they were free from cardiovascular and pulmonary diseases. They were put to one of two groups: control group (n=20) where the insufflation of oxygen via face mask was used for preoxygenation and via nasal catheters after tracheal extubation; research group (n=20) where after preoxygenation via face mask the insufflation of oxygen was additionally used with a speed of 5 l/min through nasopharyngeal airway 30 Fr (Rusch®) during the next apnea and first two hours after extubation. After laryngoscopy and guaranteed visualization of the vocal cords it was allowed to continue the apnea until SpO2 decreased to 95% or since the beginning of apnea 4 minutes passed, then patients were intubated and ventilated with positive end expiratory pressure of 5 cm H2O and use of 100% oxygen. Saturation during apnea was measured by using finger pulse oximeter monitor Vismo (Nihon Kohden, Japan). After the surgery all the patients were extubated in the operating room and transferred to intensive supervision ward of a surgery department where respiratory сapnographic monitoring was performed to them by the help of the device Cap-ONE (Nihon Kohden, Japan). The end points of the research were: time of the safe apnea, incidence of dyspnea during first 10 minutes after extubation and the quantity of hypoventilation cases during first 2 hours after surgery of patients from control and research groups. Statistical analysis was provided with a program Statistica for Windows version 6.0. Demographic and clinical data of the patients, basic SpO2 before preoxygenation did not significantly differ between two groups (p>0,05). In control group (n=20) during apnea all the patients had an average saturation decrease from 100% to 95% in 144±25 sec; in research group (n=20) SpO2 didn’t decrease lower than 95% during 4 min in 17 (85%) patients (p<0,05). In 3 (15%) patients from research group with BMI>40 kg/m2 the decrease of the level of blood oxygen saturation to 95% occurred after 153 sec, 165 sec and 187 sec. During the first 10 minutes after tracheal extubation the respiratory depression was inspected in all patients from both groups. In control group dyspnea occurred in average 10 (7-12) times, in 18 (90%) patients trigger RR<8/min or apnea >20 sec worked out with a gradual decrease of the level of ETCO2 in a form of almost straight line that confirmed an obstructive character of hypoventilation. In research group as in the control group the quantity of dyspnea episodes was 10 (6-11) times but all the patients had a gradual increase of the level of ETCO2 with the normal shape of capnographic curve (p<0,05) that confirmed the absence of obstruction. The same trend of the ventilation changes was determined during first 2 hours after surgery in both groups. So we found that in patients with obesity perioperative protection and oxygenation of airways by the use of nasopharyngeal airway is a simple and effective technique of the increase of safe apnea time before tracheal intubation and the prevention of obstruction of the upper airways during the recovery after anesthesia.
Место назофарингеальной протекции и оксигенации в периоперационном управлении дыхательными путями пациентов с ожирением
Nasopharyngeal protection and oxygenation in perioperative airway management of obesity patients
Keywords: ожиріння; протекція дихальних шляхів; апноетична оксигенація; назофарингіальний повітровід; ожирение; протекция дыхательных путей; апноэтическая оксигенация; назофарингеальный воздуховод; obesity; airway protection; apneic oxygenation; nasopharyngeal airway